Constitutional reforms and the balance of power: examining recent trends in strengthening democratic governance - Muhammad Ar. Husein; Amin Bendar (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This article examines recent trends in constitutional reforms and their impact on the balance of power within democratic governance. Constitutional reforms play a crucial role in shaping the distribution of power among the executive, legislative, and judicial branches of government, aiming to enhance transparency, accountability, and the rule of law. The study explores various reforms implemented globally, highlighting their successes and challenges in strengthening democratic institutions. It particularly focuses on reforms aimed at curbing executive overreach, enhancing legislative oversight, and safeguarding judicial independence. By analyzing these reforms across different political contexts, the article provides a comprehensive overview of how constitutional changes can promote or hinder democratic governance. The findings indicate that while constitutional reforms can effectively balance power and prevent authoritarianism, their success largely depends on the specific political environment, the strength of democratic institutions, and the presence of a robust civil society. In countries with strong democratic traditions and active civil societies, reforms have been more successful in enhancing checks and balances and promoting transparency and accountability. Conversely, in contexts where political elites resist democratic changes or where institutions are weak, reforms may be co-opted to consolidate power and undermine democratic principles. The study also underscores the importance of involving civil society in the reform process to ensure inclusiveness and legitimacy. Overall, the article contributes to the understanding of constitutional reforms as tools for democratic consolidation, highlighting the need for careful design and implementation to achieve the desired outcomes. It suggests that future research should continue to explore the dynamics of constitutional change to develop more effective strategies for strengthening democratic governance worldwide.